Effects of Light and Nutrition Manipulations on Thermal Respiratory Acclimation and Nocturnal Dynamics of Leaf Dark Respiration. (2nd December 2018) - Dillaway, Dylan N.; Tyree, Michael C.; Jackson, John K.
Abstract : The ability of a plant to acclimate metabolically to thermal changes is necessary to maintain a positive carbon balance. It is likely that a plant's acclimatory potential is a function of leaf nitrogen and/or leaf carbohydrate status. Two important issues assessed concerning leaf dark respiration ( R D ) were the effects of growth temperature, light, and fertilization on thermal respiratory acclimation and changes in respiratory parameters (indicative of acclimation) throughout the dark period. Soybean ( Glycine max (L.) Merr.) plants were grown in greenhouses under a full factorial treatment arrangement of temperature, light, and nutrition. R D was measured at three temperatures to estimate respiratory parameters (cool respiration R 13, warm respiration R 25, and the temperature response of respiration E O ) three times throughout the night (6 pm, 11 pm, and 4 am). Respiratory parameters did not differ throughout the night. Thermal acclimation was observed in warm grown plants under optimal growing conditions (i.e., high light and high fertilization); however, acclimation did not occur when limitations were imposed (i.e., shade or no fertilization). These findings suggest thermal acclimation will occur so long as plants do not undergo limitations. This may have major implications for natural ecosystems and may play a role in assessing an ecosystems resiliency to climate change.